SIMULASI PERANCANGAN ANIMASI 2D ALUR PEMBUATAN GULA CAKAR TRADISIONAL KHAS MAJALENGKA MENGGUNAKAN METODE MDLC - Aripin, Ali Maulana Hapid; Bastian, Ade (Universitas Majalengka, 2025)
Majalengka has a unique culinary heritage in the form of gula cakar, but the process of making it is rarely documented, so it could be forgotten as time goes by. This study aims to design a 2D animation that simulates the traditional process of making gula cakar as an educational and cultural preservation tool. The method used is the Multimedia Development Life Cycle (MDLC), which includes the stages of concept, design, material collection, assembly, and distribution. Data was collected through direct observation, interviews with artisans, and literature reviews, which were then translated into storyboards, character designs, and frame-by-frame animations using Blender and CapCut software. The research outcome is a 2D animated video systematically showcasing the steps of gula cakar production, from ingredient preparation, processing, to product cutting. The animation was distributed through digital platforms such as YouTube and social media to ensure widespread access. The findings indicate that a digital approach can enhance visual appeal while documenting local knowledge. Compared to conventional methods such as oral storytelling, animated media has proven more effective in conveying information, increasing appreciation, and expanding the reach of promoting Majalengka's traditional culinary culture.